The socio-political situation in Movarounnahr and the entry and spread of the science of hadith in this land, the first hadith scholars (Texas Journal of Multidisciplinary Studies, 2021)
Information about the origin of the term Movarounnahr and what it means, as well as the role of Qutayba ibn Muslim in the introduction of Islam to Movarounnahr and the views of the great scholars who grew up in Movarounnahr are widely covered.